Factors that influence the adoption of improved coconut management practices in Batticaloa district: A Logit Model Approach - Viharnaa, S.; Thivahary, G. (South Eastern University, Oluvil, Sri Lanka, 2013)
A study was conducted to investigate the factors that influence the adoption of improved coconut management practices in Batticaloa district. A random sample of 100 coconut growers was interviewed for this purpose. Logit model was used to estimate the relationship of adoption decision and the socioeconomic factors of farmers. Results showed that that farm land extent, age, membership with social organization and participation in organization activities are the most significant factors affecting the adoption of improved coconut management practices.
Keywords: Coconut growers; Coconut management practices; Logit model